Queer, Neurodivergent Access Intimacy - Nicolas Shannon Savard (The Journal of Consent-Based Performance)
This audio essay uses director Nicolas Shannon Savard's experimental approach to ensemble-based audio description in a 2023 production of JC Pankratz's Seahorse as the starting point for investigating where intimacy direction, disability aesthetics, and queer storytelling overlap. Reflections from both the director and actors involved in the production aim to model possibilities for how consent-based, trauma-informed practices can foster access intimacy in the rehearsal room and open up additional pathways to nuanced, fully human portrayals of queerness, neurodivergence, and madness on stage. The case study is framed by a discussion with disability and performance scholar Katya Vrtis, exploring the broader implications of access intimacy as an approach to creating more human-centered artistic and academic spaces.